Strategi Komunikasi dalam Pembangunan Desa Berbasis Partisipatif - Rani, Syamsul (UIN Antasari Banjarmasin, 2016)
Fakultas Dakwah dan Komunikasi IAIN AntasariThe purpose of development communication is not just to promote the development and delivery of messages of development, but more important than it is to grow, move, and maintain community participation in development. Communication strategy undertaken to increase community participation in rural development started since the foundation of society analytical skills through education and training so that they are able to recognize the problems and potential of the village, as well as the benefits of development to be done. The community is also involved in the planning, implementation and evaluation of rural development, based on the ability of the community. When this is done, the rural development will be achieved effectively and efficiently.Keywords: communication strategy, development communication, participation